Disgusts, rules and pleasures - Lorusso, Anna Maria (E|C, 2020)
At the crossroads between perception, cognition and culture, taste - in the processes of perceptual re-elaboration that presupposes, in the speeches that they define it, in the cultural models that it constructs - it seems to cry out all the analytic tools that semiotics has elaborated so far, from the tools of narrative analysis to those of tensive semiotics, from reflections on abductive dynamics and of judgment to those on translation, between cultures but also between different semiotic languages.